Who Draws the First Breath?: A Reconstruction of Empedocles' Respiration Theory. - Chondrokoukis, Michalis (Ancient Philosophy)
Suggesting a new reading of A74 in an exclusively physiological context and in combination with a new interpretation of B100, this article argues for a new reconstruction of Empedocles' respiration theory, involving two complementary and parallel respiratory processes, where the pressure of the innate heat acts together with the movement of the blood to drive the air in and out and reach all body parts and organs.